Johne’s Disease - Stokka, Gerald L.; Falkner, Gerald L.; Smith, John F.; Bierman, Patrick (My University, 1998)
Information about Johne’s disease, also known as paratuberculosis.
EP52_1998-11
Keywords: EP52; Livestock; EP